Treatment Options and Outcomes of Pediatric IBDU Compared with Other IBD Subtypes: A Retrospective Multicenter Study from the IBD Porto Group of ESPGHAN. Issue 6 (June 2016) - Aloi, Marina; Birimberg-Schwartz, Liron; Buderus, Stephan; Hojsak, Iva; Fell, John M.; Bronsky, Jiri; Veereman, Gigi; Koletzko, Sibylle; Shaoul, Ron; Miele, Erasmo; Turner, Dan; Russell, Richard K.
Abstract : Background: Inflammatory bowel disease unclassified (IBDU) is the rarest IBD subtype with treatment based on extrapolation from ulcerative colitis (UC) and Crohn's disease (CD) studies. We compared IBDU treatment choices with other colonic IBDs and explored long-term outcomes. Methods: This was a multicenter retrospective longitudinal study of 23 centers of pediatric IBD with isolated colitis, including a mild ileitis consistent with backwash. Results: Of note, 797 children (median age: 11.6 years, range: 2–18.4) were included: 250 with CD, 287 with UC, and 260 with IBDU (median follow-up: 2.8 [interquartile range: 1.6–4.2] years). IBDU differed from UC with lower corticosteroid (154 [59%] versus 204 [71%]; P = 0.004) and higher exclusive enteral nutrition use (26 [10%] versus 2 [0.6%]; P < 0.0001). Compared to patients with CD, patients with IBDU received less exclusive enteral nutrition and immunomodulators (26 [10%] versus 93 [37%]; P < 0.0001 and 67 [26%] versus 129 [52%]; P < 0.0001, respectively) but more aminosalicylates (228 [88%] versus 159 [64%]; P < 0.0001). Biological treatment was significantly higher in CD (82 [34%]) than in IBDU and UC (24 [12%] and 47 [17%], respectively; P < 0.0001). At last follow-up, 135 (69%) patients with IBDU had remission/mild disease activity compared with 100 (46%; P < 0.0001) patients with CD and 174 (64%; P = 0.3) patients with UC. Four (2%) of 194 patients with IBDU underwent surgery compared with 22 (8%) of 270 patients with UC ( P = 0.009) and 20 (8%) of 238 patients with CD ( P = 0.008). Conclusions: Children with IBDU have a lower medication burden and lower surgery rates than other IBD subtypes. The disease course at follow-up is generally mild, supporting an initial trial with 5-ASA before using more aggressive therapies. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 2 May 2016.